Skin-targeted inhibition of PPAR β/δ by selective antagonists to treat PPAR β/δ-mediated psoriasis-like skin disease in vivo. - Katrin Hack; Louise Reilly; Colin Palmer; Kevin D Read; Suzanne Norval; Robert Kime; Kally Booth; John Foerster (PLoS ONE)
We have previously shown that peroxisome proliferator activating receptor ß/δ (PPAR β/δ is overexpressed in psoriasis. PPAR β/δ is not present in adult epidermis of mice. Targeted expression of PPAR β/δ and activation by a selective synthetic agonist is sufficient to induce an inflammatory skin disease resembling psoriasis. Several signalling pathways dysregulated in psoriasis are replicated in this model, suggesting that PPAR β/δ activation contributes to psoriasis pathogenesis. Thus, inhibition of PPAR β/δ might harbour therapeutical potential. Since PPAR β/δ has pleiotropic functions in metabolism, skin-targeted inhibition offer the potential of reducing systemic adverse effects. Here, we report that three selective PPAR β/δ antagonists, GSK0660, compound 3 h, and GSK3787 can be formulated for topical application to the skin and that their skin concentration can be accurately quantified using ultra-high performance liquid chromatography (UPLC)/mass spectrometry. These antagonists show efficacy in our transgenic mouse model in reducing psoriasis-like changes triggered by activation of PPAR β/δ. PPAR β/δ antagonists GSK0660 and compound 3 do not exhibit systemic drug accumulation after prolonged application to the skin, nor do they induce inflammatory or irritant changes. Significantly, the irreversible PPAR β/δ antagonist (GSK3787) retains efficacy when applied topically only three times per week which could be of practical clinical usefulness. Our data suggest that topical inhibition of PPAR β/δ to treat psoriasis may warrant further exploration.